2008
DOI: 10.1080/10739680701724359
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Regulation of Inflammation by Human Aortic Endothelial Cells in a Linear Gradient of Shear Stress

Abstract: Objective-Atherosclerosis is a focal disease that develops at sites of low and oscillatory shear stress in arteries. This study aimed to understand how endothelial cells sense a gradient of fluid shear stress and transduce signals that regulate membrane expression of cell adhesion molecules and monocyte recruitment.Methods-Human aortic endothelial cells were stimulated with TNF-α and simultaneously exposed to a linear gradient of shear stress that increased from 0 to 16 dyne/cm 2 . Cell adhesion molecule expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 47 publications
9
84
0
Order By: Relevance
“…Ivabradine induced protection from inflammation in the aorta (exposed to flow) but did not alter the inflammatory state of EC in conditions where flow was unaltered (either in vitro or in vivo), providing strong evidence that ivabradine functions indirectly via alteration of vascular mechanics. This is consistent with in vitro studies showing that VCAM-1 expression correlates inversely with shear stress magnitude 31 .…”
Section: Discussionsupporting
confidence: 80%
“…Ivabradine induced protection from inflammation in the aorta (exposed to flow) but did not alter the inflammatory state of EC in conditions where flow was unaltered (either in vitro or in vivo), providing strong evidence that ivabradine functions indirectly via alteration of vascular mechanics. This is consistent with in vitro studies showing that VCAM-1 expression correlates inversely with shear stress magnitude 31 .…”
Section: Discussionsupporting
confidence: 80%
“…In vitro studies have confirmed the ability of ECs to alter their phenotype in response to fluid shear stress into a pro-inflammatory or proatherogenic phenotype (10,11). The recruitment and attachment of leukocyte to the endothelium is dependent on the cell phenotype and the local fluid forces acting on the circulating leukocyte (12,13). The local response of the endothelial cells and the complex hemodynamics created by the geometry of a stenosis likely plays a role in the regional attachment of leukocytes.…”
Section: Introductionmentioning
confidence: 91%
“…Figure 11. Receptor surface density versus WSS relationship determined by curve fitting to in vitro data for TNF-a stimulated CAM expression, obtained from [51]. Here, stars, squares and circles denote experimental data for ICAM-1, VCAM-1 and E-selectin, respectively, and the solid lines represent the corresponding fitted data.…”
Section: Resultsmentioning
confidence: 99%
“…These CAMs, in particular VCAM-1, are regarded as early markers of atherosclerosis due to their upregulation at the site of inflammation. First, a phenomenological model (see appendix A) correlating CAM expression to local WSS as detailed in [16,44,51] was used to estimate the surface density of the target receptor with respect to their unstimulated expression under static conditions (see electronic supplementary material, figure S6). Spherical NPs (d p ¼ 100 nm) uniformly coated with anti-VCAM-1 antibodies (aVCAM-1 NPs) were then introduced into the bloodstream by placing a bolus of NPs at the SFA inlet as before.…”
Section: Predicting the Vascular Deposition Of Nanoparticles In The Smentioning
confidence: 99%